Answer:
541
Step-by-step explanation:
550-120+200-89=541
Answer:
I believe its 24 minutes or 30 minutes
Step-by-step explanation:
Answer:
Look it up
Step-by-step explanation:
You can look at the questions online
Answer:
Step-by-step explanation:
If you add a line of best fit, its extension is likely to intersect the y-axis between 200 and 100 but closer to 100.
The best estimate is choice C) 125
The Bernoulli equation is almost identical to the standard linear ODE.
![y'=P(x)y+Q(x)y^n](https://tex.z-dn.net/?f=y%27%3DP%28x%29y%2BQ%28x%29y%5En)
Compare to the basic linear ODE,
![y'=P(x)y+Q(x)](https://tex.z-dn.net/?f=y%27%3DP%28x%29y%2BQ%28x%29)
Meanwhile, the Riccati equation takes the form
![y'=P(x)+Q(x)y+R(x)y^2](https://tex.z-dn.net/?f=y%27%3DP%28x%29%2BQ%28x%29y%2BR%28x%29y%5E2)
which in special cases is of Bernoulli type if
![P(x)=0](https://tex.z-dn.net/?f=P%28x%29%3D0)
, and linear if
![R(x)=0](https://tex.z-dn.net/?f=R%28x%29%3D0)
. But in general each type takes a different method to solve. From now on, I'll abbreviate the coefficient functions as
![P,Q,R](https://tex.z-dn.net/?f=P%2CQ%2CR)
for brevity.
For Bernoulli equations, the standard approach is to write
![y'=Py+Qy^n](https://tex.z-dn.net/?f=y%27%3DPy%2BQy%5En)
![y^{-n}y'=Py^{1-n}+Q](https://tex.z-dn.net/?f=y%5E%7B-n%7Dy%27%3DPy%5E%7B1-n%7D%2BQ)
and substitute
![v=y^{1-n}](https://tex.z-dn.net/?f=v%3Dy%5E%7B1-n%7D)
. This makes
![v'=(1-n)y^{-n}y'](https://tex.z-dn.net/?f=v%27%3D%281-n%29y%5E%7B-n%7Dy%27)
, so the ODE is rewritten as
![\dfrac1{1-n}v'=Pv+Q](https://tex.z-dn.net/?f=%5Cdfrac1%7B1-n%7Dv%27%3DPv%2BQ)
and the equation is now linear in
![v](https://tex.z-dn.net/?f=v)
.
The Riccati equation, on the other hand, requires a different substitution. Set
![v=Ry](https://tex.z-dn.net/?f=v%3DRy)
, so that
![v'=R'y+Ry'=R'\dfrac vR+Ry'](https://tex.z-dn.net/?f=v%27%3DR%27y%2BRy%27%3DR%27%5Cdfrac%20vR%2BRy%27)
. Then you have
![y'=P+Qy+Ry^2](https://tex.z-dn.net/?f=y%27%3DP%2BQy%2BRy%5E2)
![\dfrac{v'-R'\dfrac vR}R=P+Q\dfrac vR+R\dfrac{v^2}{R^2}](https://tex.z-dn.net/?f=%5Cdfrac%7Bv%27-R%27%5Cdfrac%20vR%7DR%3DP%2BQ%5Cdfrac%20vR%2BR%5Cdfrac%7Bv%5E2%7D%7BR%5E2%7D)
![v'=PR+\left(Q+\dfrac{R'}R\right)v+v^2](https://tex.z-dn.net/?f=v%27%3DPR%2B%5Cleft%28Q%2B%5Cdfrac%7BR%27%7DR%5Cright%29v%2Bv%5E2)
Next, setting
![v=\dfrac{u'}u](https://tex.z-dn.net/?f=v%3D%5Cdfrac%7Bu%27%7Du)
, so that
![v'=\dfrac{uu''-(u')^2}{u^2}](https://tex.z-dn.net/?f=v%27%3D%5Cdfrac%7Buu%27%27-%28u%27%29%5E2%7D%7Bu%5E2%7D)
, allows you to write this as a linear second-order equation. You have
![\dfrac{uu''-(u')^2}{u^2}=PR+\left(Q+\dfrac{R'}R\right)\dfrac{u'}u+\dfrac{(u')^2}{u^2}](https://tex.z-dn.net/?f=%5Cdfrac%7Buu%27%27-%28u%27%29%5E2%7D%7Bu%5E2%7D%3DPR%2B%5Cleft%28Q%2B%5Cdfrac%7BR%27%7DR%5Cright%29%5Cdfrac%7Bu%27%7Du%2B%5Cdfrac%7B%28u%27%29%5E2%7D%7Bu%5E2%7D)
![u''-\left(Q+\dfrac{R'}R\right)u'+PRu=0](https://tex.z-dn.net/?f=u%27%27-%5Cleft%28Q%2B%5Cdfrac%7BR%27%7DR%5Cright%29u%27%2BPRu%3D0)
![u''+Su'+Tu=0](https://tex.z-dn.net/?f=u%27%27%2BSu%27%2BTu%3D0)
where
![S=-\left(Q+\dfrac{R'}R\right)](https://tex.z-dn.net/?f=S%3D-%5Cleft%28Q%2B%5Cdfrac%7BR%27%7DR%5Cright%29)
and
![T=PR](https://tex.z-dn.net/?f=T%3DPR)
.